Trading Rules and Excess Volatility - Bulkley, George; Tonks, Ian (Journal of Financial and Quantitative Analysis, 1992)
A number of recent papers have reported evidence that stock prices are more volatile than is consistent with efficient markets. We argue that the excess volatility tests address a definition of efficient markets that makes an extreme information assumption. We go on to test a weaker definition of efficient markets, due to Jensen (1978). We show the existence of a profitable trading rule that earns a significantly higher rate of return than a buy-and-hold strategy, and so conclude that stock prices are too volatile, even when judged by this weaker definition.